Clinical management and outcome of extreme preterm infant with respiratory distress syndrome, early onset sepsis and necrotizing enterocolitis stage 1: a case report - Priya, A.; Fardan, Mohammed; Shaji, Aswathy M.; Kannan, R.; Yadav, K. Arun Chander (International Journal of Basic & Clinical Pharmacology, 2021)
Respiratory distress syndrome, although it is common in extreme preterm infants, early and effective management will aid in better outcome. Preterm also comes with multiple co- morbidities which has to be considered and stepwise treatment is utmost important in tackling them. Here, we report a case of an extreme preterm baby who experienced respiratory distress syndrome with early onset sepsis along with necrotizing enterocolitis. Early diagnosis and management helped in the discharge of the infant in stable condition.